2017
DOI: 10.1159/000475912
|View full text |Cite
|
Sign up to set email alerts
|

Mir-338-3p Mediates Tnf-A-Induced Hepatic Insulin Resistance by Targeting PP4r1 to Regulate PP4 Expression

Abstract: Objective: Insulin resistance is a critical factor contributing to the pathogenesis of type 2 diabetes and other metabolic diseases. Recent studies have indicated that miR-338-3p plays an important role in cancer. Here, we investigated whether miR-338-3p mediates tumour necrosis factor-α (TNF-α)-induced hepatic insulin resistance. Methods: The activation of the insulin signalling pathway and the level of glycogenesis were examined in the livers of the db/db and high fat diet (HFD)-fed mice and in HEP1-6 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 39 publications
2
32
0
1
Order By: Relevance
“…In our previous study, it was demonstrated that treatment with TNF-α decreased miR-338-3p expression levels and suppressed the activation of the AKT/GSK pathway in the livers of mice (13). In the present study, treatment with TNF-α significantly decreased the level of p-FOXO1/FOXO1 and significantly increased the protein and mRNA expression levels of genes associated with gluconeogenesis in the livers of mice, including PGC-1α, G6Pase and PEPCK ( Fig.…”
Section: Tnf-α Treatment Induces Gluconeogenesis In Mouse Livers and supporting
confidence: 64%
See 4 more Smart Citations
“…In our previous study, it was demonstrated that treatment with TNF-α decreased miR-338-3p expression levels and suppressed the activation of the AKT/GSK pathway in the livers of mice (13). In the present study, treatment with TNF-α significantly decreased the level of p-FOXO1/FOXO1 and significantly increased the protein and mRNA expression levels of genes associated with gluconeogenesis in the livers of mice, including PGC-1α, G6Pase and PEPCK ( Fig.…”
Section: Tnf-α Treatment Induces Gluconeogenesis In Mouse Livers and supporting
confidence: 64%
“…targetscan.org/), Pictar (http://www.pictar.org/) and miRanda (http://microrna.org/) databases were used to predict that PP4R1 was a target of miR-338-3p. The miR-338-3p binding site with in the PP4R1 3'-UTR was verified and in previously study (13). The PP4R1 3'-UTR fragment, including the miR-338-3p binding site was cloned from mouse liver cells and inserted into pmirGLO vector (Promega Corporation, Madison, WI, USA).…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 65%
See 3 more Smart Citations